Otoritas Penafsiran Al-Qur'an di Era Artificial Intelligence: Tantangan dan Peluang - Agus Agus Rifki Ridwan; Aghnia Faradits; Ferry Heryadi; Muyasaroh Muyasaroh; Irmawati Irmawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyse the authority of Qur’anic interpretation in the era of Artificial Intelligence (AI) and to identify the challenges and opportunities arising from the use of this technology in tafsir studies. This study employs a library research method with a qualitative-descriptive approach through the analysis of various literature related to Qur’anic exegesis, religious authority, and the development of artificial intelligence. The findings show that AI has expanded public access to tafsir information, increased the efficiency of searching for Islamic sources, and supported the wider dissemination of Qur’anic knowledge. However, the use of AI also presents challenges, including limitations in understanding the historical, linguistic, and methodological contexts of interpretation, as well as the potential for bias and information inaccuracy. This study concludes that AI cannot replace the authority of mufassirs in interpreting the Qur’an, but it can be used as a supporting instrument in learning and tafsir research. Therefore, AI must be used critically and responsibly while maintaining scholarly competence as the primary foundation of interpretation.